ANALISIS EFEKTIVITAS PENERIMAAN PENDAPATAN DAERAH KOTA MAKASSAR TAHUN 2024 BERDASARKAN DATA DJPK KEMENKEU - Andi Nurrahma Gaffar; Adriansyah Adriansyah; Yulia Yunita Yusuf; Andi Faisal; Asmar Asmar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effectiveness of regional revenue collection in Makassar City for the year 2024 based on official data from the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. The research employs a descriptive quantitative approach focusing on three main components of regional revenue: Local Own-Source Revenue (PAD), Transfers to Regions and Village Funds (TKDD), and Other Legitimate Revenues. The analysis is conducted by calculating the effectiveness ratio between budget realization and targets to assess the region’s fiscal performance. The results show that the overall effectiveness of Makassar City’s regional revenue reaches 82.46%, categorized as moderately effective. Specifically, PAD records an effectiveness of 67.41% (less effective), TKDD 104.77% (highly effective), and Other Legitimate Revenues 59.14% (ineffective). The dominance of TKDD in total revenue indicates a continued high fiscal dependence on the central government, while the relatively low contribution of PAD reflects weaknesses in tax administration and suboptimal digitalization of local financial systems. These findings emphasize that the current level of fiscal effectiveness does not yet reflect ideal fiscal independence. Therefore, the Makassar City Government needs to strengthen PAD enhancement strategies through digitalized tax collection, diversification of revenue sources, institutional capacity building, and performance-based fiscal transfer reforms. These efforts are expected to improve revenue effectiveness and promote sustainable fiscal independence.